Elaboration de cookies diététiques à base de farine de souchet comestible et de bactéries probiotiques. - Kassous, Wafa; Djourdem, Nabila (My University, 2022)
In this study, we propose the development of dietetic cookies made with 100% wholemeal flour of edible nutsedge, enriched or not, with 5% honeybee syrup containing probiotic bacteria. A semi-native panel calculated and evaluated the technological characteristics of the flour as well as the physical and sensory criteria of the cookies. Our findings revealed that the crude flour made from nutsedge tubers had the typical bulk density (0.74g/ml) and dispersibility (68%) of this plant. while the water absorption capacity (0.08 g/ml) was lower than previously reported data. Our prepared flour had a high capacity for oil absorption and foaming. Furthermore, we determined that the edible Tiger Nut flour was gluten-free. Physical examination of the cookies revealed no differences in weight, diameter, thickness, or spread ratio between the sugar-free cookie and the honey-syrup-containing probiotic cookie. Furthermore, when compared to commercial cocoa cookies of the DELIGHT brand, both cookies were made in accordance with international standards. At the first tasting, the global sensory analysis revealed that the cookies enriched with honey syrup outperformed those without sugar in terms of sensory quality, taste, color, and smell, as well as general acceptability. After 15 days, the appreciation shifted in favor of the sugar-free cookies. The CIE LAB trichromatic analysis of the edible nutsedge cookies without sugar or with honey-syrup reflected the diet cookie's distinctive dark color. The panelists judged our cookies stored for 15 days as having the characteristic taste of the product using the hedonic test, and no negative connotation was recorded. The color of the honey syrup-soaked cookies was judged to be darker (d1/d15: 40/25 percent) than those without sugar. The texture analysis attributed the noticeable crunchiness, even though the analysis also revealed differences in hardness values between the two categories of cookies, which decreased during storage. Finally, our honey syrup-enriched cookies served as an excellent vehicle for our probiotic isolate, which expressed a viability of 6.43 log CFU per cookie. More research is needed to better understand the nutritional composition of these cookies
Keywords: Diet cookie; edible nutsedge; flour; physical analysis; sensory analysis; probiotic